2021
DOI: 10.1029/2021jc017434
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ocean Color Niche Selection by Synechococcus Blue‐Green Acclimaters

Abstract: The terms generalist and specialist in ecology refer to organisms with differences in tolerance or preference for food or habitat-generalists having weaker preferences and wider tolerances. Examples are abundant in the literature and range from generalist bird species able to adapt to disturbed environments (Viol et al., 2012) to the broad feeding habits of fish in Arctic lakes (Laske et al., 2018). Among photosynthetic organisms in aquatic environments, feeding and habitat preferences translate into nutrient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…The chromatic acclimating Synechococcus requires approximately six generations, equivalent to several days, to adjust their PUB/PEB ratio in response to the prevailing ambient light color Palenik, 2001;Shukla et al, 2012). Previous study suggested that the vertical transport of water in the upwelling zone aligned with this chromatic acclimation process (Lovindeer et al, 2021). It was estimated that eddies with maximum SLA >0.5 cm possess a vertical velocity of up to 50 m day 1 , while weak eddies (maximum SLA <0.2 cm) have a vertical velocity of up to 15 m day 1 (Pilo et al, 2018).…”
Section: Different Ecological Niches For the Two Chromatic Acclimatorsmentioning
confidence: 99%
“…The chromatic acclimating Synechococcus requires approximately six generations, equivalent to several days, to adjust their PUB/PEB ratio in response to the prevailing ambient light color Palenik, 2001;Shukla et al, 2012). Previous study suggested that the vertical transport of water in the upwelling zone aligned with this chromatic acclimation process (Lovindeer et al, 2021). It was estimated that eddies with maximum SLA >0.5 cm possess a vertical velocity of up to 50 m day 1 , while weak eddies (maximum SLA <0.2 cm) have a vertical velocity of up to 15 m day 1 (Pilo et al, 2018).…”
Section: Different Ecological Niches For the Two Chromatic Acclimatorsmentioning
confidence: 99%